Identification of a new probiotic strain, Lactiplantibacillus plantarum VHProbi® V38, and its use as an oral health agent - Zhang, Jingyan; Duan, Zhi (Frontiers in Microbiology, 2022)
Probiotics can be used to treat oral diseases such as dental caries, gingivitis, periodontitis, and halitosis. This study identified a probiotic strain from fermented cabbages that has a strong inhibitory effect on Streptococcus mutans, one of the primary pathogenic bacteria responsible for dental caries. The strain was identified and tested for its oral health properties. The API 50CH system and 16S rDNA sequencing verified that this was a new strain and it was given the name, Lactiplantibacillus plantarum VHProbi®V38. Agglutination, growth inhibition and adhesion, and biofilm removal tests indicated that L. plantarum VHProbi® V38 inhibited and reduced S. mutans. This probiotic was shown to have a broad antibacterial spectrum, simultaneously inhibiting the growth of periodontal pathogenic bacteria such as Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Fusobacterium nucleatum. After 2 hours of co-cultivation with these pathogens, L. plantarum VHProbi® V38 was able to significantly reduce adhesion to human primary gingival epithelial (HPGE) cells. These findings suggest that this L. plantarum strain can prevent and treat periodontal diseases caused by these pathogenic bacteria. L. plantarum VHProbi® V38 also adheres strongly to HPGE cells and thus has potential as an oral probiotic. This study describes new methods that can be used to aid the screening and identification of oral probiotics.